History in Public: Public Past in Present Culture of Concepts - Danyal Masood, (Dialogue Social Science Review (DSSR), 2024)
This article is a theoretical understanding with the viewpoint about the implication of history in public as discourse of radical trust for social reconstruction and representational cultural materialism. The positions of the past have been long debated in the intellectual landscape. However, the present relations of past in contemporary culture of concepts marked an important site after the emergence of public history in the second half of twentieth century. Historical theory after cultural turn has intensely affected the concepts of modernist historiographical writings which challenge objectivity. The relation of past and objectivity have an important discussion in historical studies which expended multiple perspectives. This article tried to reenact the concepts and interpretations of historical with the lived and perceived past to better understand in the methodological complication of history in public regarding sources authority, authenticity of narrative, re-interpretations of inaccessible stories, and role of memory in the development of public consciousness. This article is an attempt to reconnect the ontology of academic historical Studies with public history in the presence of post-concept culture which has already suspended the regime of traditional truth and objectivity.